Necrotizing Sialometaplasia Associated with Orthodontic Appliance: A Case Report - , Mariana Botelho Leite; , Kaio Henrique Soares; , Sâmia Francy Ferreira Alves; , Lara Moreira Jalles Milani; , Gabriela Ferreira Zanon Simões; , Ana Terezinha Marques Mesquita (Archives of Current Research International, 2025)
Necrotizing Sialometaplasia (NS) is a rare, self-limiting inflammatory condition primarily affecting the minor salivary glands of the palate, accounting for less than 1% of salivary gland diseases. Trauma-induced ischemia and chemical irritation, particularly from gastric acid reflux, have been suggested as potential contributing factors. This study presents a case of NS in a 17-year-old female following the placement of a palatal breaker appliance, exploring its possible association with mechanical trauma and comparing it with existing literature.